Analysis of N.O. okerblom’s method for computerized determination of the deflection of welded I-beams - Bela, Sabo (Journal of Production Engineering, 2023)
The article describes the analysis of N.O. Okerblom’s method for the computational determination of the deflection of welded I-beams. Through a comparison between calculated and measured deflections, the accuracy of the applied computational methods is examined.